TEMPORADA DE HURACANES DE FERNANDA MELCHOR O LA EXPRESIÓN DE LAS NUEVAS RURALIDADES MEXICANAS - GEORGES MOUKOUTI ONGUEDOU (Revue Hybrides, 2023)
This article deals with the new Mexican ruralities in Temporada de huracanes (2017), novel by Fernanda Melchor. The study aims to locate the story describing the rural spaces, to analyze how the inventoried spaces articulate the new ruralities and, finally, to emphasize the ideological configuration of the story around the new ruralities. To carry it out, we resort to the methodological proposals of Mitterrand (1980) collected by Soubeyroux (1985b) on the analysis of the fictional space. The methodological guidelines of these critics help us to establish our essay in the inventory, the functioning and the ideological symbolism of the spaces. From this analysis, it turns out that Mexican ruralities are inherent to a spatial dialectic, which configures the relationships and worldviews of the Mexican rural environment.